Pengaruh Disiplin Kerja, Lingkungan Kerja Fisik, dan Kolaborasi Tim terhadap Kinerja Karyawan Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Bandung - Lusiana, Irna; Muttaqin, Ridlwan; Farida, Ida (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine work discipline, physical work environment, and team collaboration on employee performance at the Bandung Regency Human Resources Development and Personnel Agency (BKPSDM). The research method used in this study is a quantitative research method with descriptive and verification approaches. Data were obtained through primary data sources collected through distributing questionnaires to respondents, and secondary data. The research sample consisted of 60 employees. The collected data were then analyzed using statistical techniques including descriptive analysis, verification analysis, discriminative coefficient analysis and partial and simultaneous hypothesis testing using the SPSS 26 program. The results of the study indicate that work discipline has a significant effect on employee performance, the physical work environment does not have a significant effect on employee performance, team collaboration has a significant effect on employee performance, and work discipline, physical work environment, and team collaboration together have a positive and significant effect on employee performance.